Analysis of the Absolute and Relative Values of the Tools for Jump Preparation per Mesocycles in the Women's Triple Jump Discipline - Tereza MARINOVA (Editura Universitatii Transilvania din Brasov, 2018)
The objective of this study is to improve the management of the triple jump workout for women, analyzing the preparation of Teresa Marinova, Olympic, World and European champion in the discipline. As a basis for analysis we chose the year when the athlete achieved the greatest success in her career, i.e. the Olympic title during the 1999/2000 sports competition season. Analyzes may result in an improved training process in the women's triple jump. The effectiveness of the sports shape management in highly qualified athletes is determined not only by the applied cumulative workload volumes but also by the rational load organization in the individual mesocycles of the macrocycle. In this publication, they are presented and analyzed as follows: Absolute values of the tools for jump preparation per mesocycles during the 1999-2000 sports competition season and Relative values of the tools for jump preparation per mesocycles during the 1999-2000 sports competition season (%).